2021
DOI: 10.1186/s13054-021-03776-2
|View full text |Cite
|
Sign up to set email alerts
|

Fever and hypothermia represent two populations of sepsis patients and are associated with outside temperature

Abstract: Background Fever and hypothermia have been observed in septic patients. Their influence on prognosis is subject to ongoing debates. Methods We did a secondary analysis of a large clinical dataset from a quality improvement trial. A binary logistic regression model was calculated to assess the association of the thermal response with outcome and a multinomial regression model to assess factors associated with fever or hypothermia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
13
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 47 publications
2
13
0
Order By: Relevance
“…In infectious diseases, endogenous and exogenous heat sources lead to an increased body temperature, which is the response of the body against exogenous microorganisms ( 34 ). It has also been found that hypothermia increases the occurrence of adverse outcomes in septic patients, which is consistent with our findings ( 35 ).…”
Section: Discussionsupporting
confidence: 93%
“…In infectious diseases, endogenous and exogenous heat sources lead to an increased body temperature, which is the response of the body against exogenous microorganisms ( 34 ). It has also been found that hypothermia increases the occurrence of adverse outcomes in septic patients, which is consistent with our findings ( 35 ).…”
Section: Discussionsupporting
confidence: 93%
“… 8 , 9 In the real world, afebrile bacteraemia was often observed in immunocompromised individuals, 6 and the first-line physician frequently reported the episodes of hypothermia in critically ill patients. 10 Although numerous studies have previously reported that initial hypothermia or afebrile status results in unfavourable outcomes in patients experiencing sepsis or bacteraemia, 6 , 11 the evidence is limited regarding the comparisons of the prognostic effect of delayed AAT between bacteraemia patients with initial presentation of hypothermia, normothermia, and high febrile status. We hypothesised that the prognostic impact of delayed AAT differed in bacteraemia patients presenting with different iBTs.…”
Section: Introductionmentioning
confidence: 99%
“…The predominance of either excessive pro-inflammatory responses or immunosuppression in sepsis also seems to be associated with two opposing states of thermoregulation. In a recent study, Thomas-Rüddel et al determined two subsets of septic patients, one with pronounced fever and another with hypothermia [ 28 ]. These phenotypes where associated with environmental temperature lending support to our assumption of a link between energy expenditure and resistance or disease tolerance, respectively [ 29 ].…”
Section: Introductionmentioning
confidence: 99%